Pengaruh Diet Tinggi Kolesterol terhadap Kadar TNF α - Reza Adityas Trisnadi; Joko Wahyu Wibowo; Siti Thomas Zulaikhah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Dyslipidemia is a lipid metabolism disorder in the form of increased levels of total cholesterol, low density lipoproteins (LDL), triglycerides, and decreased high density lipoproteins (HDL). The cause of dyslipidemia in Indonesia is the behavior of people who tend to consume foods low in fiber and high in fat. A diet that is high in cholesterol, as well as an unhealthy lifestyle, stress, smoking makes blood fat levels very difficult to control which can lead to hypercholesterolemic conditions. Eating foods with lots of fat will increase the inflammatory process, namely TNF α. The purpose of this study was to determine the impact of a high cholesterol diet on TNF α levels. The method used was experimental design with post test only control group design on the experimental animal rat Galur Wistar. Rats will be given a diet high in cholesterol, namely quail egg yolks for 7 days. Examination of TNF α levels using ELISA technique. The results of the examination gott a p-value